Rotator cuff - Poehling, Gary; Burkhart, Stephen S., 1949- (St. Louis : Mosby, 1999)
(Producer) Learn the anatomy of the rotator cuff by viewing dissections; review the biomechanics of the rotator cuff by looking at anatomical mpdels; learn how expert surgeons use various techniques to repairs rotator cuff problems; listen to'pearls' from expert surgeons on what to look for, what to avaid, and how to avoid them.
CD is available at Koleksi Media, Perpustakaan HUKM
System requirements: IBM compatible 133 MHz Pentium computer (166 MHz or faster recommended); 16 MB RAM (32 MB recommended), 10 MB hard disk space; Windows 95; 4x CD-ROM drive (8x or faster recommended); video card capable of 800 x 600 resolution at 16-bit col.--high col. (32-bit col.--true col. recommended); sd. card with speakers; 28.8 or faster modem and Web browser program such as Netscape Navigator 4.0 (or newer) or Microsoft Internet Explorer (or newer) optional for Internet.
System requirements: PowerMac 80 MHz computer (120 MHz or faster recommended); 16 MB RAM (32 MB recommended), 10 MB hard disk space; MacOS7.1 (or newer); 4x CD-ROM drive (8x or faster recommended); video card capable of 800 x 600 resolution at 16-bit col.--high col. (32-bit col.--true col. recommended); sd. card with speakers; 28.8 or faster modem and Web browser program such as Netscape Navigator 4.0 (or newer) or Microsoft Internet Explorer (or newer) optional for Internet.
Keywords: Rotator Cuff -- CD-ROM; Arthroscopy -- CD-ROM